Nitric oxide–an antidote to seed aging modifies meta-tyrosine content and expression of aging-linked genes in apple embryos - Ciacka, Katarzyna; Tyminski, Marcin; Wal, Agnieszka; Gniazdowska, Agnieszka; Krasuska, Urszula (Frontiers in Plant Science, 2022)
Short-term (3 h) treatment of embryos isolated from accelerated aged apple seeds (Malus domestica Borkh.) with NO partially reduced the effects of aging. The aim of the study was to investigate the impact of the short-term NO treatment of embryos isolated from apple seeds subjected to accelerated aging on the expression of genes potentially linked to the regulation of seed aging. Apple seeds were artificially aged for 7, 14, or 21 days. Then the embryos were isolated from the seeds, treated with NO, and cultured for 48 h. Progression of seeds aging was associated with the decreased transcript levels of most of the analyzed genes (Lea1, Lea2a, Lea4, Hsp70b, Hsp20a, Hsp20b, ClpB1, ClpB4, Cpn60a, Cpn60b, Raptor, and Saur). The role of NO in the mitigation of seed aging depended on the duration of the aging. After 7 and 14 days of seed aging, a decreased expression of genes potentially associated with the promotion of aging (Tor, Raptor, Saur) was noted. NO-dependent regulation of seed aging was associated with the stimulation of the expression of genes encoding chaperones and proteins involved in the repair of damaged proteins. After NO application, the greatest upregulation of ClpB, Pimt was noted in the embryos isolated from seeds subjected to 7-day long accelerated aging, Hsp70b, Hsp70c, Cpn in the embryos of seeds aged for 14 days, and Lea2a in the embryos of seeds after 21 days of aging. We also demonstrated the increased meta-tyrosine concentration in respect to the progression of artificial aging, and the NO-induced increased phenylalanine content in seeds artificially aged for 21 days. In the NO-treated embryos of seeds aged for 7 and 21 days, the level of tyrosine was almost doubled compared to aged tissue. Our data confirmed the usage of meta-tyrosine as a marker of seed aging and indicated that the increased meta-tyrosine/tyrosine ratio could be related to loss of seed viability.